Assessment of human adipose‐derived stem cell on surface‐modified silicone implant to reduce capsular contracture formation - Chanutchamon Sutthiwanjampa; Byung Ho Shin; Na Eun Ryu; Shin Hyuk Kang; Chan Yeong Heo; Hansoo Park (Wiley, 2022)
Abstract Medical devices made from poly(dimethylsiloxane) (PDMS)‐based silicone implants have been broadly used owing to their inert properties, biocompatibility, and low toxicity. However, long‐term implantation is usually associated with complications, such as capsular contracture due to excessive local inflammatory response, subsequently requiring implant removal. Therefore, modification of the silicone surface to reduce a risk of capsular contracture has attracted increasing attention. Human adipose‐derived stem cells (hASCs) are known to provide potentially therapeutic applications for tissue engineering, regenerative medicine, and reconstructive surgery. Herein, hASCs coating on a PDMS (hASC‐PDMS) or itaconic acid (IA)‐conjugated PDMS (hASC‐IA‐PDMS) surface is examined to determine its biocompatibility for reducing capsular contracture on the PDMS surface. In vitro cell cytotoxicity evaluation showed that hASCs on IA‐PDMS exhibit higher cell viability than hASCs on PDMS. A lower release of proinflammatory cytokines is observed in hASC‐PDMS and hASC‐IA‐PDMS compared to the cells on plate. Multiple factors, including in vivo mRNA expression levels of cytokines related to fibrosis; number of inflammatory cells; number of macrophages and myofibroblasts; capsule thickness; and collagen density following implantation in rats for 60 days, indicate that incorporated coating hASCs on PDMSs most effectively reduces capsular contracture. This study demonstrates the potential of hASCs coating for the modification of PDMS surfaces in enhancing surface biocompatibility for reducing capsular contracture of PDMS‐based medical devices.